The Implementation Of Reflective Teaching Practice By Indonesian EFL Teachers - Nur Sellyta; Rahmah Fithriani (South Sulawesi Education Development (SSED), 2024)
Reflective teaching is one strategy to improve professional development for teachers so that the teaching and learning process is more effective and efficient. This study aimed to find out how Indonesian EFL teachers implement reflective teaching in their classrooms, the impact of implementing reflective teaching, and what difficulties are faced when implementing reflective teaching. This study employed a qualitative, descriptive case study approach. A questionnaire and interviews were used to collect data from 18 teachers, which were then analysed using thematic content analysis. Based on the findings of the research, in the implementation of reflective teaching by EFL teachers, there are five ways: use reflective journals, ask for feedback from students, collaborate with colleagues, record videos, and record audio. Better preparation, improved teacher-student interaction, and improved classroom management are the three effects that EFL teachers notice after implementing reflective teaching. There are three teacher difficulties in implementing reflective teaching: time and workload, lack of peers to collaborate, and knowledge of reflection methods.